Preparation of nanostructure Ni doped CdO thin films by sol gel spin coating method - Yakuphanoğlu, Fahrettin (Springer, 2011)
The nanostructure Ni-doped CdO films have been prepared by sol gel spin coating method. Atomic force microscopy results indicate that the CdO films are formed from the nanoparticles and the grain size is changed with nickel content. X-ray diffraction patterns of the films indicate that the undoped and Ni-doped CdO films have polycrystalline structure with a cubic sodium chloride structure, showing two main characteristic peaks assigned to the (111) and (200) planes. The optical band gap values of undoped and Ni-doped CdO films were determined by optical absorption method. The E-g values of the CdO films were found to be in the range of 2.26-2.60 eV. The E-g values of the CdO films increase with the content of Ni dopant (up to 6% Ni). It is evaluated that the optical band gap and grain size of the CdO film can be controlled by doping with nickel atoms.
International Conference on Sol-Gel Processes for Advanced Ceramics (SGPAC-2009) -- OCT 11-14, 2009 -- Indira Gandhi Ctr Atom Res, Kalpakkam, INDIA
Keywords: Nanostructure CdO film; Optical; Sol gel